Quantitative Assessment of Foreign Direct Investment (FDI) and Its Contribution to Employment Growth - Ayewumi Ezonfade Fredrick; Okoro Godsday Edesiri (Review of International Economic, Taxation, and Regulations, 2025)
The research analysed the impact of foreign direct investment on employment growth through quantitative assessment.   A retrospective research design was employed to explore this relationship, focussing on the Nigerian economy.   Data from the Central Bank of Nigeria Statistical Bulletin and World Bank Indicators spanning from 1998 to 2023 were utilised for the study.   Various statistical tests such as descriptive, correlation, heteroskedasticity, and multicollinearity were conducted using E-Views 9.0. Ordinary Least Squares regression was used to analyse the influence of different factors on employment in Nigeria. Findings indicate that despite GDP growth, employment gains in the Nigerian economy remain insufficient. FDI inflows are not translating into job creation, likely because investments are focused on capital-intensive sectors. Labor force participation is not leading to more employment, indicating a lack of job opportunities and structural unemployment issues. Manufacturing output does not significantly boost employment, reflecting challenges in the industrial sector. The study recommends that, Nigeria needs policies that encourage foreign direct inflows into labor-intensive sectors and inclusive growth strategies that prioritize employment creation, such as: Boosting labor-intensive industries like agriculture, manufacturing, and construction. Investing in technical education and skill acquisition to match labor demand. Encouraging SMEs and entrepreneurship, which are major job creators.